Biochemical analysis of microbiotas obtained from healthy, prediabetic, type 2 diabetes, and obese individuals - Duzgun, Cagla; Dede, Sureyya; Karakus, Emine; Adas, Mine; Bilen, Omer (WALTER DE GRUYTER GMBH, 2023)
Objectives In this study, we aimed to evaluate the intestinal and urinary microbiota diversity of obese, pre-diabetic, diabetic, and healthy subjects together with their food consumption frequency and investigate the effect on glucose metabolism. Methods DNA was isolated from stool and urinary samples of fifteen obese, fifteen prediabetics, fifteen type 2 diabetic, and fifteen lean participants by using the quantitative real-time polymerase chain reaction (qPCR) method. The amounts of Bifidobacterium, Bacteroides, and Firmicutes were measured and food consumption frequency was answered by all participants through a questionnaire. Results The levels of Bifidobacterium in fecal microbiota were significantly higher in type 2 diabetic patients compared with lean (p=0.034), prediabetic (p=0.009), and obese participants (p=0.012). However, the levels of Bifidobacterium in urinary microbiota were decreased in obese, prediabetic, and type 2 diabetic subjects as controls (p=0.048; p=0.038; p=0.015 respectively). Additionally, Bacteroides/Firmicutes ratio decreased in type two diabetic patients compared with lean subjects and had a negative correlation with BMI in prediabetic subjects. Food consumption frequency illustrates that lean subjects have unhealthy eating habits. Conclusions Urinary microbiota could be considered in the future context of a potential biomarker in the progress of type 2 diabetes and obesity.
Keywords: microbiota; obesity; prediabetes; real-time qPCR; type 2 diabetes; GUT MICROBIOTA; DIET; Biochemistry & Molecular Biology